2014
DOI: 10.7150/ijbs.8739
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mitochondrial Genomes of Carcinoscorpius rotundicauda and Tachypleus tridentatus (Xiphosura, Arthropoda) and Implications for Chelicerate Phylogenetic Studies

Abstract: Horseshoe crabs (order Xiphosura) are often referred to as an ancient order of marine chelicerates and have been considered as keystone taxa for the understanding of chelicerate evolution. However, the mitochondrial genome of this order is only available from a single species, Limulus polyphemus. In the present study, we analyzed the complete mitochondrial genomes from two Asian horseshoe crabs, Carcinoscorpius rotundicauda and Tachypleus tridentatus to offer novel data for the evolutionary relationship within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Different gene rearrangements in the mitochondrial genome is relatively common in crustacean species (Shen et al, 2007), and are probably caused by slipped-strand mispair and gene deletions (Yamauchi et al, 2003). Nine 1-to 7-bp overlaps and 13 intergenic spacers that were between 1 and 30 bp in length were found, which in general is similar to that reported in other species' mitochondrial genomes (Ma et al, 2013;Baek et al, 2014;Wang et al, 2014). The A + T contents of the different regions ranged from 66.79% (protein-coding region) to 76.22% (control region), and the overall A + T content was 68.72%, which is similar to that in C. japonica, Scylla olivacea, and S. serrata (Table 2).…”
Section: Genome Organizationsupporting
confidence: 71%
See 1 more Smart Citation
“…Different gene rearrangements in the mitochondrial genome is relatively common in crustacean species (Shen et al, 2007), and are probably caused by slipped-strand mispair and gene deletions (Yamauchi et al, 2003). Nine 1-to 7-bp overlaps and 13 intergenic spacers that were between 1 and 30 bp in length were found, which in general is similar to that reported in other species' mitochondrial genomes (Ma et al, 2013;Baek et al, 2014;Wang et al, 2014). The A + T contents of the different regions ranged from 66.79% (protein-coding region) to 76.22% (control region), and the overall A + T content was 68.72%, which is similar to that in C. japonica, Scylla olivacea, and S. serrata (Table 2).…”
Section: Genome Organizationsupporting
confidence: 71%
“…Complete mitochondrial genome sequence information is useful in studying genome-level characteristics and phylogenetic relationships (Knudsen et al, 2006), because of its high mutation rate, simple structure, abundant distribution, and maternal inheritance (Yu et al, 2012;Ma et al, 2013;Baek et al, 2014). With the development of molecular techniques, it has become easier to obtain complete mitochondrial genome sequences (Wang et al, 2015), and they have been reported in many crustacean species (Shen et al, 2007;Liu and Cui, 2010;Jondeung et al, 2012;Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ten gene overlaps and ten intergenic spacers were found in mitochondrial genome of C. feriata , most of them have been reported in many other species mitochondrial genomes 23 24 47 . The total length of overlaps and intergenic spacers were 24 and 105 bp, with ranges from 1 to 7 and from 2 to 27 bp, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Mitochondrial genome is a typically closed-circular molecule ranging approximately from 14 to 18 kb in size, and it consists of 13 protein-coding genes, 22 transfer RNA (tRNA) genes, 2 rRNA genes, and a control region. It is thought to be an ideal marker for studies on population genetic diversity, molecular phylogeny, and species identification because of its high mutation rate, simple structure, abundant distribution, and maternal inheritance 22 23 24 . Thus far, complete mitochondrial genomes have been reported in many crustacean species, such as Litopenaeus vannamei 25 , C. japonica 21 , Scylla serrata 26 , and S. paramamosain 23 .…”
mentioning
confidence: 99%
“…Recently, molecular techniques are considered the most precise and quick methods for identification (Marshall, 2005). A mitochondrial genome is a common tool in studying species identification, molecular phylogeny and population genetic diversity (Ma et al, 2013;Baek et al, 2014). One of the most important mitochondrial genomes is the Cytochrome Oxidase subunit I (COI) gene due to its effort in various genetic studies (Buhay, 2009).…”
Section: Introductionmentioning
confidence: 99%